GARP is a key molecule for mesenchymal stromal cell responses to TGF‐β and fundamental to control mitochondrial ROS levels. (19th February 2020) - Carrillo‐Gálvez, Ana Belén; Gálvez‐Peisl, Sheyla; González‐Correa, Juan Elías; de Haro‐Carrillo, Marina; Ayllón, Verónica; Carmona‐Sáez, Pedro; Ramos‐Mejía, Verónica; Galindo‐Moreno, Pablo; Cara, Francisca E.; Granados‐Principal, Sergio; Muñoz, Pilar; Martin, Francisco; et al.
Abstract: Multipotent mesenchymal stromal cells (MSCs) have emerged as a promising cell therapy in regenerative medicine and for autoimmune/inflammatory diseases. However, a main hurdle for MSCs‐based therapies is the loss of their proliferative potential in vitro. Here we report that glycoprotein A repetitions predominant (GARP) is required for the proliferation and survival of adipose‐derived MSCs (ASCs) via its regulation of transforming growth factor‐β (TGF‐β) activation. Silencing of GARP in human ASCs increased their activation of TGF‐β which augmented the levels of mitochondrial reactive oxygen species (mtROS), resulting in DNA damage, a block in proliferation and apoptosis. Inhibition of TGF‐β signaling reduced the levels of mtROS and DNA damage and restored the ability of GARP −/low ASCs to proliferate. In contrast, overexpression of GARP in ASCs increased their proliferative capacity and rendered them more resistant to etoposide‐induced DNA damage and apoptosis, in a TGF‐β‐dependent manner. In summary, our data show that the presence or absence of GARP on ASCs gives rise to distinct TGF‐β responses with diametrically opposing effects on ASC proliferation and survival. Abstract : Silencing of glycoprotein A repetitions predominant (GARP) in adipose‐derived mesenchymal stromal cells (ASCs) increases the activation of transforming growth factor‐β (TGF‐β), resulting in mitochondrial reactive oxygen species‐dependent DNA damage, inhibition of proliferation, and apoptosis. In contrast, overexpression of GARP induces a TGF‐β response characterized by an increased resistance to DNA damage, increased proliferation, and a reduction in apoptosis. We show that GARP is critical in controlling TGF‐β activation/signaling in ASCs during in vitro expansion.